1987
DOI: 10.1111/j.1365-2621.1987.tb14253.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Coefficients to Liquids with Food Particles in Axially Rotating Cans

Abstract: Heat transfer rates were measured for steam-heated, rotating cans containing potato spheres in water. Can rotational speed (9.3-101 rpm), sphere size (22.2-35.0 mm), and potato volume fraction (0.107-0.506) were varied in 14 triplicated experiments. Overall heat transfer coefficients were correlated within 225% with physical properties and operating variables by an equation derived by dimensional analysis. Film coefficients (h,) for heat transfer from the water to potatoes in the can were determmed by thermoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 8 publications
1
54
1
Order By: Relevance
“…He was unable to explain the reason behind this negligible effect. Deniston et al (1987) determined the heat transfer rates to steam-heated, axially rotating cans containing potato spheres in water. They attributed the insensitivity of h fp to can rotational speed (9.3-29.1-101 rpm) to three experimental conditions resulting in small changes in relative particle-fluid velocity: (1) closeness of density of potato particle (1,063 kg/m 3 ) to that of water, so that particle settling due to gravity was minimal; (2) since the particle was located at the can center, centrifugal force acting on it was small; and (3) stiffness of the thermocouple wire hindered the particle motion.…”
Section: Effect Of Rotational Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…He was unable to explain the reason behind this negligible effect. Deniston et al (1987) determined the heat transfer rates to steam-heated, axially rotating cans containing potato spheres in water. They attributed the insensitivity of h fp to can rotational speed (9.3-29.1-101 rpm) to three experimental conditions resulting in small changes in relative particle-fluid velocity: (1) closeness of density of potato particle (1,063 kg/m 3 ) to that of water, so that particle settling due to gravity was minimal; (2) since the particle was located at the can center, centrifugal force acting on it was small; and (3) stiffness of the thermocouple wire hindered the particle motion.…”
Section: Effect Of Rotational Speedmentioning
confidence: 99%
“…They attributed this to the decreased relative particle-to-fluid velocity due to the drag exerted on the fluid by the particles. Deniston et al (1987) reported a slight increase in h fp with increasing particle volume fraction, which was lowered for higher particle contents. They attributed this to the tight packing in the can (higher particle volume fraction), which restricted the particle free movement.…”
Section: Effect Of Particle Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the proper design and successful optimization of the rotational retort process, a felicitous methodology to predict particle lethality during processing is extremely helpful. Several studies have been conducted on the evaluation of heat transfer to canned liquid particulate mixtures in end-over-end rotation (Lekwauwa and Hayakawa 1986;Sablani and Ramaswamy 1995, 1996, 1997, 1998, 1999Krishnamurthy et al 2000;Meng and Ramaswamy 2005); however, there are very few studies available to determine U and h fp in axial mode of rotation (Lenz and Lund 1978;Hassan 1984;Deniston et al 1987;Fernandez et al 1988;Stoforos andMerson 1990, 1991). Furthermore, there are several limitations associated with the axial mode methods applied to predict lethality during heating for the real food particle system with finite internal and surface resistance to heat transfer (0.1<N Bi <40).…”
Section: Introductionmentioning
confidence: 96%
“…Similar to the traditional thermal processing, it is also necessary for the particles and fluid to receive the predetermined minimum heat treatment in the form of minimum process lethality (F o ) during agitation processing. In order to predict the heat penetration data and to fully understand and mathematically describe the mechanism of heat transfer in liquid particle systems, it is necessary to have data on the associated heat transfer coefficients (Deniston et al 1987;Hassan 1984;Merson and Stoforos 1990). For the proper design and successful optimization of the rotational retort process, a felicitous methodology to predict particle lethality during processing is extremely helpful.…”
Section: Introductionmentioning
confidence: 99%